1996
DOI: 10.1161/01.str.27.1.63
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Stroke in Middle-Aged Patients With Non–Insulin-Dependent Diabetes

Abstract: Our prospective population-based study gives evidence that previous history of stroke, hypertension, hyperglycemia, and dyslipidemia are strong predictors of stroke in middle-aged patients with NIDDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
145
1
5

Year Published

1999
1999
2007
2007

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 223 publications
(167 citation statements)
references
References 36 publications
16
145
1
5
Order By: Relevance
“…The magnitude of the effect of diabetes and stroke on stroke risk probably depends on the duration of the disease, and this time factor may operate differently for diabetes than for stroke. Among the patients who have survived an acute stroke, the risk of subsequent stroke event is highest immediately after the attack and the risk stabilizes over time, whereas among diabetic subjects, the stroke risk increases with the duration of the disease [15]. As in the baseline cohort analyses of our study, most previous studies have not paid attention to the time of stroke event or duration of diabetes in their data analyses.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The magnitude of the effect of diabetes and stroke on stroke risk probably depends on the duration of the disease, and this time factor may operate differently for diabetes than for stroke. Among the patients who have survived an acute stroke, the risk of subsequent stroke event is highest immediately after the attack and the risk stabilizes over time, whereas among diabetic subjects, the stroke risk increases with the duration of the disease [15]. As in the baseline cohort analyses of our study, most previous studies have not paid attention to the time of stroke event or duration of diabetes in their data analyses.…”
Section: Discussionmentioning
confidence: 86%
“…Several studies have recently assessed the relationship between type 2 diabetes and the risk of stroke. Type 2 diabetes has been shown to be an independent risk factor for stroke morbidity [15,[18][19][20][21][22] and mortality [14,16,17,22,40]. The Renfrew and Paisley Study found that type 2 diabetes was a predictor of stroke incidence among women but not among men [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Wong et al showed that after the age of 75 years, patients with diabetes had the same risk of stroke as those without diabetes [2]. The evidence for an increase in risk with smoking and obesity in people with diabetes is conflicting [3,[7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Part of the variation in the published risk estimates for stroke in people with diabetes may be explained by the composition of the study populations [2,3,9,14]. Many studies excluded older patients, did not differentiate between diabetes type, selected from a population that had a different underlying risk of stroke from that of the UK or used the general population containing diabetes as the comparison group [9,10,13,14].…”
Section: Introductionmentioning
confidence: 99%